A method for preparing aluminum-plastic composite film for lithium battery

By adding specific ingredients to the heat sealing layer of the aluminum-plastic composite film and subjecting it to gamma ray irradiation treatment, the problem that the heat-sealing layer of the existing aluminum-plastic composite film is prone to deterioration when in contact with the lithium battery electrolyte is solved, and the film's durability is significantly improved. Electrolyte resistance and peel strength enhance the safety of battery packaging materials.

CN115503318BActive Publication Date: 2025-01-21NINGBO JEEAO CHUANGYI NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211242704.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-11
Publication Date
2025-01-21
Estimated Expiration
2042-10-11

AI Technical Summary

Technical Problem

When the heat sealing layer of the existing aluminum-plastic composite film comes into contact with the lithium battery electrolyte, it is easy to cause the electrolyte to deteriorate, thereby reducing the heat sealing strength of the packaging material and affecting battery safety.

Method used

A new heat sealing layer preparation method is used by mixing titanium oxide, methoxypolyoxyethylene acrylate, vinylguanamine, nickel acrylate, deionized water and benzoyl peroxide and other ingredients, and then irradiated by gamma rays and vacuum drying to form a heat seal layer with improved corrosion resistance and peel strength.

Benefits of technology

This method significantly improves the electrolyte resistance and peel strength of the aluminum-plastic composite film, slows down the corrosion of the aluminum foil layer by corrosive liquids in the battery, and enhances the safety of battery packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003885284990000101
    Figure BDA0003885284990000101
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum-plastic composite films, and in particular to a method for preparing an aluminum-plastic composite film for a lithium battery. The method adopts titanium oxide, methoxypolyethylene oxide acrylate, vinylguanamine and nickel acrylate to perform surface modification on a polypropylene film, and the modified polypropylene film is then irradiated with gamma rays and composited with nylon / aluminum foil through an adhesive to obtain the aluminum-plastic composite film for a lithium battery. The aluminum-plastic composite film prepared by the invention has high peeling strength between an aluminum foil layer and a heat-sealing layer (polypropylene film), improves the barrier property and electrolyte resistance of a lithium battery soft packaging material, and ensures that the lithium battery has stability for long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum-plastic composite films, in particular to a method for preparing an aluminum-plastic composite film for a lithium battery. Background Art

[0002] Aluminum-plastic composite film comprehensively utilizes the extremely high barrier properties of metal aluminum foil and the softness of plastic film in microstructure, and prepares packaging materials with two-dimensional structure, environmental protection advantages and performance advantages through composite process. As an important material for soft-packaging lithium battery cell packaging, aluminum-plastic composite film has been rapidly developed in the packaging of lithium battery products and is widely used in consumer electronics, new energy vehicles, power tools, medical equipment, drones and other fields.

[0003] Chinese patent CN201710966920.2 discloses an aluminum-plastic composite film for lithium battery soft packaging, comprising: a wear-resistant layer, a first adhesive layer, an aluminum foil layer, a passivation layer, a second adhesive layer with corrosion resistance, and a heat-sealing layer arranged in sequence from the outside to the inside, wherein the passivation layer comprises the following components in parts by weight: 100 parts of acrylic resin, 5-15 parts of chromium-containing compounds, 1-5 parts of phenyltrimethylsilane coupling agents, 1-5 parts of titanate coupling agents, and 30-50 parts of water; the second adhesive layer with corrosion resistance comprises the following components in parts by weight: 100 parts of acid-modified polyolefin resin, 1-5 parts of epoxy system curing agent, 1-5 parts of fluorine-containing micropowder, 10-20 parts of cyclohexane solvent, and 20-40 parts of butanone solvent.

[0004] Chinese patent CN201911324754.1 discloses a lithium battery soft packaging material and a preparation method thereof. The lithium battery soft packaging material comprises a substrate layer, a first adhesive layer, an aluminum foil layer, a corrosion-resistant coating provided on at least one surface of the aluminum foil layer, a second adhesive layer and a heat-sealing layer; the corrosion-resistant coating comprises rare earth oxide / conductive polymer composite nanoparticles and epoxy resin.

[0005] Chinese patent CN201610672133.2 discloses a thermally conductive aluminum-plastic composite film for lithium-ion battery soft packaging and a manufacturing method thereof, wherein a surface protection layer, a thermally conductive material layer, an upper adhesive, an upper passivation barrier layer, an aluminum film layer, a lower passivation barrier layer, a lower adhesive, and a CPP composite film layer are sequentially stacked on the thermally conductive aluminum-plastic film; the steps include: pre-treating both sides of the base material, coating the pre-treated side of the base material, washing the surface of the aluminum foil, coating the upper passivation barrier layer and the lower passivation barrier layer, the upper adhesive, and the lower adhesive.

[0006] Since the heat-sealing layer of the aluminum-plastic composite film is in direct contact with the electrolyte in the battery cell, the deterioration of the electrolyte will cause battery safety problems due to the decrease in the heat-sealing strength of the packaging material. It is necessary to strengthen material permeability monitoring during production and use to avoid the influence of moisture and oxygen on the electrolyte and battery. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing an aluminum-plastic composite film for a lithium battery, and the preparation method is as follows:

[0008] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0009] The heat sealing layer preparation method is:

[0010] According to the mass proportions, 7-14 parts of titanium oxide, 6-14 parts of methoxypolyethylene oxide acrylate, 0.01-0.1 parts of vinylguanamine, 0.5-2.2 parts of nickel acrylate, 30-40 parts of deionized water, 0.2-1.6 parts of benzoyl peroxide, and 80-100 parts of solvent are weighed, mixed evenly, heated to 40-50° C., 22-30 parts of polypropylene film are added, and after soaking, the film is taken out and dried to obtain a polypropylene film having a surface coated with a methoxypolyethylene oxide acrylate monomer; after being irradiated with gamma rays at room temperature, a heat sealing layer is obtained.

[0011] The drying conditions are as follows: drying in a vacuum drying oven at 40-60° C. for 10-20 min.

[0012] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0013] The compounding machine is a dry compounding machine, and the compounding conditions are as follows: the temperatures of the three-stage oven are set to 50-60°C, 70-80°C, and 80-90°C, respectively; the compounding speed is 50-60m / min; the curing temperature is 70-90°C, the curing time is 16-22h; the aging temperature is 50-55°C, the aging time is 50-70h; and the lithium battery soft packaging material is obtained after cutting and packaging.

[0014] The isolation layer is a PA (nylon) layer with a thickness of 22-35 μm.

[0015] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 10 to 40 μm.

[0016] The adhesive is a two-component polyurethane adhesive with a thickness of 5 to 20 μm.

[0017] The solvent is acetone.

[0018] The soaking time is 4-8 minutes.

[0019] The gamma ray irradiation dose rate is 55-80 Gy / min.

[0020] The irradiation time is 3-6 minutes.

[0021] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:

[0022] 1. Compared with the commonly used polyolefin film, the acrylic nickel on the skeleton of the aluminum-plastic composite film prepared by the present invention can slow down the corrosion of the corrosive liquid in the battery on the surface of the aluminum foil layer.

[0023] 2. The aluminum-plastic composite film prepared by the present invention has better peeling strength and electrolyte resistance than the commonly used polyolefin film. DETAILED DESCRIPTION

[0024] The present invention is further described below with reference to specific examples, but is not limited thereto. The experimental methods described in the following examples, unless otherwise specified, are conventional methods well known to those skilled in the art; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0025] Example 1

[0026] The present invention provides a method for preparing an aluminum-plastic composite film for a lithium battery, and the preparation method comprises:

[0027] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0028] The heat sealing layer preparation method is as follows:

[0029] Weigh 7kg of titanium oxide, 6kg of methoxypolyethylene oxide acrylate, 0.01kg of vinylguanamine, 0.5kg of nickel acrylate, 30kg of deionized water, 0.2kg of benzoyl peroxide, and 80kg of solvent, mix them evenly, heat them to 40°C, add 22kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0030] The heat-sealing layer is dried in a vacuum drying oven at 40° C. for 10 min.

[0031] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0032] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 50°C, 70°C, and 80°C respectively, the compounding speed is 50m / min, the curing temperature is 70°C, the curing time is 16h, the aging temperature is 50°C, the aging time is 50h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0033] The isolation layer is a PA (nylon) layer with a thickness of 22 μm.

[0034] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 10 μm.

[0035] The adhesive is LIOFOL 2775-21 two-component solvent-based polyurethane adhesive with a thickness of 5 μm.

[0036] The solvent is acetone.

[0037] The soaking time is 4 minutes.

[0038] The gamma ray irradiation dose rate is 55 Gy / min.

[0039] The irradiation time is 3 minutes.

[0040] Example 2

[0041] The present invention provides a method for preparing an aluminum-plastic composite film for a lithium battery, and the preparation method comprises:

[0042] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0043] The heat sealing layer preparation method is:

[0044] Weigh 8 kg of titanium oxide, 7 kg of methoxypolyethylene oxide acrylate, 0.03 kg of vinylguanamine, 0.7 kg of nickel acrylate, 32 kg of deionized water, 0.6 kg of benzoyl peroxide, and 90 kg of solvent, mix them evenly, heat them to 42° C., add 25 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0045] The heat-sealing layer is dried in a vacuum drying oven at 42° C. for 12 minutes.

[0046] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0047] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 52°C, 72°C, and 82°C respectively, the compounding speed is 53m / min, the curing temperature is 72°C, the curing time is 18h, the aging temperature is 52°C, the aging time is 60h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0048] The isolation layer is a PA (nylon) layer with a thickness of 25 μm;

[0049] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 20 μm;

[0050] The adhesive is FL-7511A two-component polyurethane adhesive with a thickness of 10 μm; and the solvent is acetone.

[0051] The soaking time is 5 minutes.

[0052] The gamma ray irradiation dose rate is 60 Gy / min.

[0053] The irradiation time is 4 minutes.

[0054] Example 3

[0055] The present invention provides a method for preparing an aluminum-plastic composite film for a lithium battery, and the preparation method comprises:

[0056] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0057] The heat sealing layer preparation method is as follows:

[0058] Weigh 10 kg of titanium oxide, 10 kg of methoxypolyethylene oxide acrylate, 0.05 kg of vinylguanamine, 1.2 kg of nickel acrylate, 36 kg of deionized water, 0.8 kg of benzoyl peroxide, and 95 kg of solvent, mix them evenly, heat them to 48° C., add 28 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0059] The heat-sealing layer is dried in a vacuum drying oven at 55° C. for 15 min.

[0060] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0061] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 57°C, 76°C, and 86°C respectively, the compounding speed is 57m / min, the curing temperature is 84°C, the curing time is 20h, the aging temperature is 55°C, the aging time is 70h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0062] The isolation layer is a PA (nylon) layer with a thickness of 32 μm;

[0063] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 30 μm;

[0064] The adhesive is TL-7418 / HD205 two-component polyurethane adhesive with a thickness of 12 μm;

[0065] The solvent is acetone.

[0066] The soaking time is 7 minutes.

[0067] The gamma ray irradiation dose rate is 70 Gy / min.

[0068] The irradiation time is 5 minutes.

[0069] Example 4

[0070] The present invention provides a method for preparing an aluminum-plastic composite film for a lithium battery, and the preparation method comprises:

[0071] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0072] The heat sealing layer preparation method is as follows:

[0073] Weigh 14 kg of titanium oxide, 14 kg of methoxypolyethylene oxide acrylate, 0.1 kg of vinylguanamine, 2.2 kg of nickel acrylate, 40 kg of deionized water, 1.6 kg of benzoyl peroxide, and 100 kg of solvent, mix them evenly, heat them to 50° C., add 30 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0074] The heat-sealing layer is dried in a vacuum drying oven at 60° C. for 20 minutes.

[0075] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0076] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 60°C, 80°C, and 90°C respectively, the compounding speed is 60m / min, the curing temperature is 90°C, the curing time is 22h, the aging temperature is 54°C, the aging time is 55h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0077] The isolation layer is a PA (nylon) layer with a thickness of 35 μm;

[0078] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 40 μm;

[0079] The adhesive is FL-7511A two-component polyurethane adhesive with a thickness of 20 μm;

[0080] The solvent is acetone.

[0081] The soaking time is 8 minutes.

[0082] The gamma ray irradiation dose rate is 80 Gy / min.

[0083] The irradiation time is 6 minutes.

[0084] Comparative Example 1

[0085] A method for preparing an aluminum-plastic composite film for a lithium battery, the operating steps of which are:

[0086] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0087] The heat sealing layer preparation method is:

[0088] Weigh 8 kg of titanium oxide, 0.03 kg of vinylguanamine, 0.7 kg of nickel acrylate, 32 kg of deionized water, 0.6 kg of benzoyl peroxide, and 90 kg of solvent, mix them evenly, heat them to 42° C., add 25 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film coated with methoxypolyethylene oxide acrylate monomer on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0089] The heat-sealing layer is dried in a vacuum drying oven at 42° C. for 12 minutes.

[0090] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0091] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 52°C, 72°C, and 82°C respectively, the compounding speed is 53m / min, the curing temperature is 72°C, the curing time is 18h, the aging temperature is 52°C, the aging time is 60h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0092] The isolation layer is a PA (nylon) layer with a thickness of 25 μm;

[0093] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 20 μm;

[0094] The adhesive is FL-7511A two-component polyurethane adhesive with a thickness of 10 μm; and the solvent is acetone.

[0095] The soaking time is 5 minutes.

[0096] The gamma ray irradiation dose rate is 60 Gy / min.

[0097] The irradiation time is 4 minutes.

[0098] Comparative Example 2

[0099] A method for preparing an aluminum-plastic composite film for a lithium battery, the operating steps of which are:

[0100] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0101] The heat sealing layer preparation method is as follows:

[0102] Weigh 8 kg of titanium oxide, 7 kg of methoxypolyethylene oxide acrylate, 0.7 kg of nickel acrylate, 32 kg of deionized water, 0.6 kg of benzoyl peroxide, and 90 kg of solvent, mix them evenly, heat them to 42° C., add 25 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0103] The heat-sealing layer is dried in a vacuum drying oven at 42° C. for 12 minutes.

[0104] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0105] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 52°C, 72°C, and 82°C respectively, the compounding speed is 53m / min, the curing temperature is 72°C, the curing time is 18h, the aging temperature is 52°C, the aging time is 60h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0106] The isolation layer is a PA (nylon) layer with a thickness of 25 μm;

[0107] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 20 μm;

[0108] The adhesive is FL-7511A two-component polyurethane adhesive with a thickness of 10 μm; and the solvent is acetone.

[0109] The soaking time is 5 minutes.

[0110] The gamma ray irradiation dose rate is 60 Gy / min.

[0111] The irradiation time is 4 minutes.

[0112] Comparative Example 3

[0113] A method for preparing an aluminum-plastic composite film for a lithium battery, the operating steps of which are:

[0114] The composite film comprises an isolation layer, an aluminum foil layer and a heat sealing layer.

[0115] The heat sealing layer preparation method is:

[0116] Weigh 8 kg of titanium oxide, 7 kg of methoxypolyethylene oxide acrylate, 0.03 kg of vinylguanamine, 32 kg of deionized water, 0.6 kg of benzoyl peroxide, and 90 kg of solvent, mix them evenly, heat them to 42° C., add 25 kg of polypropylene film, soak them, take them out and dry them to obtain a polypropylene film with methoxypolyethylene oxide acrylate monomer coated on the surface; after irradiating them with gamma rays at room temperature, a heat sealing layer is obtained.

[0117] The heat-sealing layer is dried in a vacuum drying oven at 42° C. for 12 minutes.

[0118] When the isolation layer coated with adhesive comes out of the oven and is slightly cooled, it is pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composite nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature curing room for curing.

[0119] The compounding machine is a dry compounding machine, and the compounding conditions are: the temperatures of the three-stage oven are set to 52°C, 72°C, and 82°C respectively, the compounding speed is 53m / min, the curing temperature is 72°C, the curing time is 18h, the aging temperature is 52°C, the aging time is 60h, and the lithium battery soft packaging material is obtained after cutting and packaging.

[0120] The isolation layer is a PA (nylon) layer with a thickness of 25 μm;

[0121] The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 20 μm;

[0122] The adhesive is FL-7511A two-component polyurethane adhesive with a thickness of 10 μm;

[0123] The solvent is acetone.

[0124] The soaking time is 5 minutes.

[0125] The gamma ray irradiation dose rate is 60 Gy / min.

[0126] The irradiation time is 4 minutes.

[0127] Example and comparative example test results:

[0128] The aluminum-plastic composite films prepared in the above Examples 1-4 and Comparative Examples 1-3 were tested using the following test method.

[0129] 1. Interlayer peel strength test

[0130] The interlayer peel strength of the aluminum foil layer and the heat seal layer was tested according to the test method specified in GB / T 2792-2014 "Test method for peel strength of adhesive tapes". The peeling angle was 180° and the peeling speed was 150 mm / min.

[0131] 2. Electrolyte resistance test

[0132] The aluminum-plastic composite film sample strips prepared in each example with a size of 100 mm×15 mm were immersed in an electrolyte at 85°C for 15 days, and the interlayer peeling strength between the aluminum foil layer and the heat sealing layer was tested again, with a peeling angle of 180° and a peeling speed of 150 mm / min.

[0133] The test conditions of the above-mentioned electrolyte are specifically as follows: after immersing the 100mm×15mm aluminum-plastic composite film sample strips prepared in each example in an 85°C electrolyte [13g of lithium hexafluorophosphate is added to 100g of ethylene carbonate / diethyl carbonate / dimethyl carbonate=1 / 1 / 1 (volume ratio)] for 15 days, the aluminum-plastic composite film sample strips are taken out and washed with deionized water, the water is wiped off with a wipe paper, the moisture is fully dried, and then the interlayer peel strength test between the CPP film and the aluminum foil is carried out.

[0134]

[0135] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing an aluminum-plastic composite film for a lithium battery, characterized in that: The aluminum-plastic composite film comprises an isolation layer, an aluminum foil layer and a heat-sealing layer. The preparation method of the heat-sealing layer is as follows: according to the mass fraction, 7-14 parts of titanium oxide, 6-14 parts of methoxy polyoxyethylene acrylate, 0.01-0.1 parts of vinyl guanamine, 0.5-2.2 parts of nickel acrylate, 30-40 parts of deionized water, 0.2-1.6 parts of benzoyl peroxide, and 80-100 parts of solvent are weighed, mixed evenly, heated to 40-50° C., and 22-30 parts of polypropylene film are added. After soaking, take out and dry to obtain a polypropylene film with methoxy polyoxyethylene acrylate monomer coated on the surface; after being placed under γ-ray irradiation at room temperature, a heat sealing layer is obtained; the isolation layer coated with the adhesive comes out of the oven and is slightly cooled and then pressed with the aluminum foil; the adhesive is applied to the aluminum foil side of the composite film and dried; after cooling, it is composited with the heat sealing layer using a composite machine; the composited nylon / aluminum foil / heat sealing layer composite film is placed in a constant temperature aging chamber for aging; the composite machine is a dry composite machine, and the composite conditions are: the three-stage oven temperatures are set to 50-60°C, 70-80°C, and 80-90°C, respectively, the composite speed is 50-60m / min, the curing temperature is 70-90°C, the curing time is 16-22h, the aging temperature is 50-55°C, the aging time is 50-70h, and the lithium battery soft packaging material is obtained after cutting and packaging; the γ-ray irradiation dose rate is 55-80Gy / min.

2. The method for preparing an aluminum-plastic composite film for lithium batteries according to claim 1, characterized in that: The drying conditions are as follows: drying in a vacuum drying oven at 40-60° C. for 10-20 min.

3. The method for preparing an aluminum-plastic composite film for lithium batteries according to claim 1, characterized in that: The isolation layer is a PA (nylon) layer with a thickness of 22-35 μm.

4. The method for preparing an aluminum-plastic composite film for a lithium battery according to claim 1, characterized in that: The aluminum foil layer is a soft aluminum foil, which is pure aluminum or aluminum alloy, and has a thickness of 10 to 40 μm.

5. The method for preparing an aluminum-plastic composite film for lithium batteries according to claim 1, characterized in that: The adhesive is a two-component polyurethane adhesive with a thickness of 5 to 20 μm.

6. The method for preparing an aluminum-plastic composite film for lithium battery according to claim 1, characterized in that: The solvent is acetone.

7. The method for preparing an aluminum-plastic composite film for lithium battery according to claim 1, characterized in that: The soaking time is 4-8 minutes.

8. The method for preparing an aluminum-plastic composite film for lithium battery according to claim 1, characterized in that: The irradiation time is 3-6 minutes.

Citation Information

Patent Citations

  • Aluminum-plastic composite film for lithium ion battery soft package and manufacturing method of aluminum-plastic composite film

    CN106346904A

  • Aluminum-plastic composite film for flexible packaging of lithium battery

    CN107825773A

  • Lithium battery flexible package material and preparation method thereof

    CN111136977A

  • Epoxy adhesion for lithium battery flexible package and lithium battery flexible package material

    CN102703010A

  • Aluminum-plastic composite film for lithium battery and preparation method of aluminum-plastic composite film

    CN112937024A